2018
DOI: 10.1016/j.foodhyd.2018.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation and characterisation of dietary fibre from blackcurrant pomace

Abstract: The potential of blackcurrant pomace as a raw material for the extraction of dietary fibre was evaluated using two pomaces one sourced from the UK and one from Poland.A fractionation protocol was designed to isolate and subsequently quantify the soluble and insoluble dietary fibre fractions. Blackcurrant pomace and isolated pectins, hemicelluloses and celluloses were assessed by means of sugar compositional analysis, spectroscopy, size exclusion chromatography and dilute solution viscometry. The blackcurrant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
93
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(105 citation statements)
references
References 64 publications
9
93
1
2
Order By: Relevance
“…This variability can be caused by several factors such as soil characteristics, climate conditions and degree of ripening of raw fruits and differences in juice pressing technology. According to Alba et al () total sugars content values were different for various origins of the material (Poland and UK). It was observed that glucose, fructose, and sucrose content decreased after extrusion process.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This variability can be caused by several factors such as soil characteristics, climate conditions and degree of ripening of raw fruits and differences in juice pressing technology. According to Alba et al () total sugars content values were different for various origins of the material (Poland and UK). It was observed that glucose, fructose, and sucrose content decreased after extrusion process.…”
Section: Resultsmentioning
confidence: 98%
“…According to the literature, protein content of the black currant pomace depends on its origin and varies from 6.9 to 15.5% (Alba et al, ; Górnaś et al, ; Juśkiewicz et al, ; Pieszka et al, ). For fruit material without seeds protein content for different harvest seasons and fraction size varies between 11.8–12.6% (Sójka & Król, ).…”
Section: Resultsmentioning
confidence: 99%
“…Spectral smoothing was applied using instrument software (OMNIC 3.1). In addition, a calibration curve with known DM values of pectin standards and their correlation with the area ratio of esterified carboxylic groups over the total carboxyl groups (esterified bands are centered around 1740 and nonesterified around 1630 cm −1 ) determined the degree of methoxylation of all pectins . A Bruker AV 500 spectrometer (Bruker Co., Fällanden, Switzerland) at 500 MHz 1 H and 125.77 MHz 13 C was used for nuclear magnetic resonance (NMR) analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The use of BCP as a means of adding fiber to processed foods offers an attractive incentive for BC producers and processors alike. A recent characterization study on BCP sourced from two different countries (Lucozade‐Ribena‐Suntory, UK and GreenField Natural Ingredients, Warsaw, Poland) reported that 25% to 30% of BCP is soluble dietary fiber (SDF; for example, pectin and some hemicelluloses), whereas approximately 47% is insoluble dietary fiber (IDF; for example, cellulose or lignin; Alba et al., ). Pure IDF was measured as being approximately 61%.…”
Section: Processing Methodsmentioning
confidence: 99%
“…Ratios for IDF/SDF were calculated for the BC from the United Kingdom and the BC from Poland as 1.9 and 1.6, respectively (Alba et al., ). The main cell wall component noted in this research was Klason lignin, which was the major insoluble fiber in both BCP (Alba et al., ). This characterization of BCP was preceded by fractions of constituent soluble and insoluble fractions followed by extractions of pectins (acid soluble and calcium soluble), alkali‐soluble lignin, alkali‐soluble hemicelluloses, and cellulose (Table ; Alba et al., ).…”
Section: Processing Methodsmentioning
confidence: 99%